2018
DOI: 10.1093/ajcp/aqy003
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Clinical Associations of Immunoassays That Detect Antibodies to Negatively Charged Phospholipids Other Than Cardiolipin

Abstract: Increasing titers of APhL, anti-PS, and anti-PI antibodies could indicate an increased risk of thrombotic and/or obstetric aPL-related manifestations. These assays may be promising biomarkers for particular APS manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Additionally, aPI IgG correlated with pre-eclampsia or premature birth, and it was also significantly correlated with stroke. Castanon et al observed a high sensitivity for aPI (41.2%-59.2%) across manifestations including thrombotic and obstetric events (18). Our previous results also demonstrated a correlation between aPI IgG and thrombosis (8).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Additionally, aPI IgG correlated with pre-eclampsia or premature birth, and it was also significantly correlated with stroke. Castanon et al observed a high sensitivity for aPI (41.2%-59.2%) across manifestations including thrombotic and obstetric events (18). Our previous results also demonstrated a correlation between aPI IgG and thrombosis (8).…”
Section: Discussionsupporting
confidence: 73%
“…Castanon et al. observed a high sensitivity for aPI (41.2%-59.2%) across manifestations including thrombotic and obstetric events ( 18 ). Our previous results also demonstrated a correlation between aPI IgG and thrombosis ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-LBPA antibodies were demonstrated in a significant number of patients with APS, however, sensitivity and specificity were lower than in aCL and anti-β2GPI [63]. Castanon et al [64] examined various aPL IgMs and IgGs in 548 serum samples using the ELISA method. Comparison of two groups of APS/healthy donors demonstrated the presence of APhL in 89.7/0%, anti-PI in 89.7/32.1%, anti-PS in 86.2/7.1%, aCL in 93.1/32.1%, and anti-β2GPI in 86.2/0%.…”
Section: Antibodies Against Phospholipid Antigensmentioning
confidence: 99%
“…Beyond the criteria anti-phospholipid antibodies (aPL) aCL and aβ2-GPI, aPL against several other anionic phospholipids (PLs) (e.g., phosphatidic acid, phosphatidyl-serine, -glycerol, -inositol), neutral PL (e.g., phosphatidyl-choline,–ethanolamine), and PL-binding proteins (e.g., annexin V, prothrombin) have been observed in APS [4, 5]. Their pathogenic role and clinical significance is not well understood and still a matter of debate [68]. These non-criteria aPL are also commonly detected with ELISA-based methods [5], which are generally less well evaluated than those for the criteria aPL [7, 9].…”
Section: Introductionmentioning
confidence: 99%